Analysis of The Influence of Customer Perceived Values, Customer Engagement, and Customer Satisfaction on Customer Loyalty - Alif Pranadetha; Syarifa Hanoum; Lissa Rosdiana Noer (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The growth of the retail business in Indonesia has led to increasing competition among industry players, pushing each to compete more aggressively in their marketing efforts. As the fashion industry in Indonesia continues to evolve, retail fashion companies are striving to create high-quality products to attract and engage customers, with the ultimate goal of fostering customer loyalty. Additionally, findings show that 118 out of 126 respondents tend to compare products from various brands before making a purchase. Therefore, this study aims to examine the relationships between customer perceived value, customer engagement, and customer satisfaction in relation to customer loyalty in the retail fashion industry. The analysis was conducted quantitatively by distributing questionnaires to 235 respondents, which were then analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that customer perceived value (including product quality, service quality, and price fairness), customer engagement, and customer satisfaction (both product and brand satisfaction) have a positive and significant relationship with customer loyalty. Based on these findings, managerial implications have been developed for the fashion retail industry to refine their strategies and enhance customer loyalty.